2014
DOI: 10.5721/eujrs20144716
|View full text |Cite
|
Sign up to set email alerts
|

Use of Unmanned Aerial Systems for multispectral survey and tree classification: a test in a park area of northern Italy

Abstract: In the frame of project FoGLIE (Fruition of Goods and Landscape in Interactive Environment), UAS were used to survey a park area in its less accessible zones, for scenic and stereoscopic videos, 3D modeling and vegetation monitoring. For this last application, specifically, through the acquisition of very high resolution images taken with two UAS-borne compact cameras (RGB and NIR), a DSM of a small vegetated area and the corresponding orthoimages were produced and co-registered. Planimetric and height accurac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 21 publications
2
52
0
2
Order By: Relevance
“…Another step would be to assess the potential of 3D mapping of the canopy surface for nest detection. 3D models can now be created using point clouds from drone imagery [74] providing better perspectives for visual interpretation of the data. Another complimentary approach would be to use light detection and ranging (LiDAR) technology.…”
Section: Discussionmentioning
confidence: 99%
“…Another step would be to assess the potential of 3D mapping of the canopy surface for nest detection. 3D models can now be created using point clouds from drone imagery [74] providing better perspectives for visual interpretation of the data. Another complimentary approach would be to use light detection and ranging (LiDAR) technology.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its very high spatial resolution (<0.1-m ground sampling distance (GSD)), UAS imagery is regularly characterized as hyperspatial imagery (Carbonneau and Piégay 2012;Greenberg et al 2005;Laliberte et al 2007;Strecha et al 2012). Many studies have taken advantage of these two characteristics, for a broad range of environmental applications, such as landslide mapping (Lucieer et al 2014), forest fire mapping (de Dios et al 2011;Merino et al 2012;Urbahs et al 2013), precision farming (Bendig et al 2013), wildlife census (Lisein et al 2013a;Vermeulen et al 2013), tree and forest characterization (Lisein et al 2013b;Zarco-Tejada et al 2014), forest biodiversity assessment (Getzin et al 2012), and forest species composition (Dunford et al 2009;Gini et al 2014). Recent studies have demonstrated the potential of UAS imagery to finely describe the forest canopy Ellis 2010, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…When a good-quality digital terrain model is available, UAS-derived photogrammetric point clouds (>10 points/m 2 ) can provide a canopy height model (CHM) with a quality comparable to light detection and ranging (LiDAR) CHM but with significant cost differences (Lisein et al 2013b). References on classification of forest species by use of UAS imagery are still rare in the literature and include only the single-date approach (Dunford et al 2009;Gini et al 2014). However, useful pioneering studies are available on vegetation mapping projects based on UAS imagery (Knoth et al 2013;Zaman et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These systems are commonly used for high-resolution surveys [29][30][31][32][33][34][35][36][37][38] as they allow flights to be performed in an automatic way [39,40]. The miniaturization of imaging and positioning sensors also reduces the payload and thus enables flights up to about one hour long [41].…”
Section: Introductionmentioning
confidence: 99%